Ultrastructure of hyphae in Gigaspora albida Schenck & Smith (Glomales) - Maia, Leonor; Kimbrough, James; Benny, Gerald (Boletín Micológico, 1994)
Studies were performed to describe the ultrastructure of hyphae in Gigaspora albida. There is an even distribution o! cytoplasmic organelles with nuclei interspaced with vacuoles and polyphosphate granules in the hyphae. Evidences indicated that nuclear condition changes after germ tube formation. No clear proof of meiotic or mitotic processes were found, but elongated nueclei, presence of nucleus associated organelles, and a line of division in the central region of some of the nuelei were demonstrated.